A study on awareness towards education insurance among Malays in Batang Kali / Nurul Hidayah Mohd Yusof - Mohd Yusof, Nurul Hidayah (2010)
Child education insurance is one of the funds or reserved made by the parents to their child for financing the child education in the tertiary level. It usually paid by the parents who become the policyholder (payor) by installment every month to insurance company. The child can be the participant starts from the age of 30 days to 18 years old (have some different in range of age for different insurance company) and will be covered with various coverage stated in the policy. Since the living cost increasing year by year, this education insurance become important and safety that needs to be owed by all parents nowadays. The main objective of this research is to identify the factors that influence awareness towards education insurance, rank the factors and recommend the most preferred factors. This research is focus only to the Malay community in Batang Kali area and 100 questionnaires had been distributed and returned completely. From the feedback gained, 33% of the respondents are male and 77% are female. The range of the respondent’s age are between 21 to 50 years. 85% of them are aware about the existence of education insurance product and 15% are not. For the research purpose, the data gained from the respondents were analyzed using Statistical Package for Social Science (SPSS) to show its reliability and validity.